Improvement of Speaking Abilities Using Sociodrama Learning Method for Islamic Studies Faculty Students - Suarni, Suarni; Baha, Tinus; Fitriah, Fitriah; Abdillah Mattinetta, Ahmad (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2022)
This study aims to improve speaking skills through sociodrama learning methods in students of the Faculty of Islamic Religion, University of Muhammadiyah Kendari. This classroom action research uses the Kemmis and Taggart models with two cycles. This study involved 44 students. Observation techniques, speaking skills tests, interviews, and documentation were used to collect data. The data are analyzed descriptively based on the characteristics of the data obtained. The results showed that learning speaking skills using the sociodrama method could improve the speaking skills of students of the Faculty of Islamic Religion in semester V of Muhammadiyah Kendari University. Improvement of speaking skills using the sociodrama method, namely (1) the average value of speaking skills in the first cycle of 75.4% increased by 10.2% from the pre-action value of 65, and the percentage of completion increased by 16.% from the pre-action percentage of 41% to 56.7%, (2) the average value of speaking skills in cycle II of 78.3 increased by 15.3 from the pre-action value of 65, and the percentage of completion increased by 36% from the pre-action percentage of 41%Â to 78%.